THE EFFECTIVENESS OF THE ORIENTATION ADMISSION PROGRAM WITH THE ASSIGNMENT OF OFFICERS IN CLASS I CIPINANG DETENTION CENTER - Fadel, Muhammad; Soge, Markus Marselinus (Universitas Nusa Cendana, 2025)
This article discusses the effectiveness of the implementation of the orientation admission program at Cipinang Class I Detention Center with the appointment of officers based on the Decree of the Head of the Detention Center. This program is designed to help new detainees adapt to the detention environment and understand their rights, obligations, and applicable rules. The research method used is descriptive qualitative with data collection techniques in the form of interviews, observations, and document analysis. The results showed that although the program has run according to standards, there are several obstacles, such as the large number of new detainees, limited facilities, and program implementation outside working hours. The assignment of officers through the Head of the Detention Center Decree has clarified the duties and responsibilities, but it is necessary to increase the number of officers and facilities to support the effectiveness of the program. Keywords: Admission Orientation; Effectiveness; AO Officer; Detainee Services; Cipinang Detention Center